Interstitial Lung Disease in Common Variable Immunodeficiency - Lopes, Joao Pedro; Ho, Hsi-en; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2021)
nterstitial lung disease (ILD) is a common complication in patients with common variable immunodeficiency (CVID) and often associated with other features, such as bronchiectasis and autoimmunity. As the ILD term encompasses different acute and chronic pulmonary conditions, the diagnosis is commonly made based on imaging features; histopathology is less frequently available. From a cohort of 637 patients with CVID followed at our center over 4 decades, we reviewed the data for 46 subjects (30 females, 16 males) who had lung biopsies with proven ILD. They had a median age at CVID diagnosis of 26.0 years old, with a median IgG level at diagnosis of 242.2 mg/dL with average isotype switched memory B cells of 0.9%. Lung biopsy pathology revealed granulomas in 25 patients (54.4%), lymphoid interstitial pneumonia in 13 patients (28.3%), lymphoid hyperplasia not otherwise specified in 7 patients (15.2%), cryptogenic organizing pneumonia in 7 patients (15.2%), follicular bronchitis in 4 patients (8.7%), and predominance of pulmonary fibrosis in 4 patients (8.7%). Autoimmune manifestations were common and were present in 28 (60.9%) patients. Nine patients (19.6%) died, with a median age at death of 49-years-old. Lung transplant was done in 3 of these patients (6.5%) who are no longer alive. These analyses reveal the high burden of this complication, with almost one-fifth of the group deceased in this period. Further understanding of the causes of the development and progression of ILD in CVID patients is required to define the best management for this patient population.